국회의원 선거제도 개혁논의와 현실적 개선방안 - 김종갑 (의정논총, 10(1), 2015)
이 논문의 목적은 2014년 헌법재판소의 국회의원 선거구 인구편차 기준에 대한 헌법불합치 결정으로 촉발된 선거제도 개혁논의의 다양한 쟁점을 살펴보고 바람직한 제도대안을 모색하는데 있다. 현행 국회의원 선거제도는 지역선거구의 비중이 비례대표보다 높기 때문에 과다한 사표발생으로 불비례성이 낮은 구조적 문제점을 보인다. 또한 특정 정당이 특정 지역에서 밀집된 지지를 바탕으로 의석을 독점하는 지역주의가 여전히 존재한다. 이밖에도 인구과밀의 도시지역은 의석이 집중되고 인구가 적은 농어촌에 할당되는 의석수는 상대적으로 적어 지역간 대표성의 불균형이 나타난다. 현재 논의되고 있는 개혁방안들은 이러한 문제점에 대해 뚜렷한 해법을 제시하지 못하고 있다. 중대선거구제는 비례성 제고의 효과는 있지만 당선인의 대표성 문제를 보여 도입되기 어렵다. 권역별 비례제의 경우 독일식과 선관위의 ‘수정’ 독일식은 높은 비례성을 보이지만 의원정수가 선거 때마다 유동적인 단점이 있고, 일본식은 의원정수를 유지할 수 있고 현행 선거제도와 정합성은 높지만 비례성이 낮다는 한계를 보인다. 석패율제의 경우 지역구도 완화의 간접적인 효과는 기대할 수 있지만, 당선인의 대표성 문제는 도입에 걸림돌이 된다. 농어촌의 지역대표성 약화에 대한 해결책으로 논의되는 방안들 중 권역별 명부작성방식과 3계층선거구제 방식은 비례의석의 절대적 규모를 높여야 된다는 점, 도농복합선거구제 도입과 비례의석 균등 할당방안은 지역간 대표성의 불균형 문제를 근본적으로 해결할 수 없다는 점, 인구기준 이원화방안은 평등선거의 원칙에 위배된다는 점 등으로 개선방안으로 고려되기 어렵다. 그러나 영호남을 교차할당하는 방식으로 전국을 3개 권역으로 할당하는 권역별 비례제는 지역주의 완화와 비례성 제고, 농어촌 지역대표성 제고에 유의미한 효과를 보일 수 있다. The purpose of this study is to analyze the various proposals regarding the reformation of the national parliament election system and propose a model that alleviates regionalism and enhances proportionality. The current system shows a low proportionality due to the low number of Proportional Representation(PR) seats. The multi-member district system tends to deliver moderately proportional results and is effective in resolving regionalism, but produces a representation problem. In the modified German PR system suggested by the National Election Commission, the assembly size fluctuates despite a relatively higher proportionality. The double candidacy system could show an alleviation of regionalism through the “Contamination effect,” but it could be subject to criticism because candidates defeated in constituency elections could be revived by PR. The mixed-district system and the equal redistribution of PR seats among regions is not an efficient solution to the problem of low representation of rural regions. The selective adaptation of the population quota tolerance limit could be unconstitutional. Thus, this study proposes a model in which the whole nation is divided into three regions, and each region elects its own PR seats. This model would play a significant role in overcoming regionalism, as it provides more opportunities for small parties and non-regional parties to win seats, and has greater proportionality than the current system according to the simulation analysis. KCI Citation Count: 8